Developing a K-12 Professional Learning Typology: Social Justice Training Designed for Educators as Adult Learners - Courtney Hoffhines (Adult Education Research Conference, 2023)
This paper examines current literature supporting the development of a K-12 professional learning typology, an original design, based in effective social justice training for educators as adult learners.
Keywords: professional learning typology; social justice; critical pedagogy; K-12